Epilepsy: Clinical Considerations in Women of Childbearing Age (Bangladesh Journal of Medical Science, 2013)
Epilepsy is the commonest chronic neurological disorder to complicate pregnancy, having an incidence of 0.15% to 10%. Sudden unexpected death in epilepsy is the principal cause of death, and seizure control is the key to minimizing this risk. The aim of antenatal care is to optimize seizure control. The lowest dose of antiepileptic medication that protects against seizures should be chosen. Non-adherence to treatment may present a greater risk to the developing fetus than antiepileptic drug exposure. Adequate rest and sleep is mandatory for epileptic women. The normal anti epileptic drug regimen should be continued during labor. An elective cesarean section should be considered if there have been frequent tonic clonic or prolonged complex partial seizures towards the end of pregnancy. Breast feeding is not contraindicated. Appropriate contraceptive advice should be given. The importance of pre conceptual care in a subsequent pregnancy should be reiterated. DOI: http://dx.doi.org/10.3329/bjms.v12i4.12818 Bangladesh Journal of Medical Science Vol. 12 No. 04 October 13 Page 364-369